Strategi Marketing Public Relations Program BRI-Incubator dalam Meningkatkan UMKM Go Global - Magdalena, Elisabeth Charoline Ria; Abdurrahman, M. Sufyan (Universitas Prof. Dr. Moestopo (Beragama), 2024)
BRI Incubator is a mentoring program carried out with RKB BUMN for all Indonesian MSMEs in order to understand financial literacy, marketing, and compete with digitalization. When using communication media to involve the public, Marketing Public Relations will emerge that fosters awareness of products and builds consumer trust in the company's image or has benefits to the marketing offered. This study aims to determine the Marketing Public Relations strategy used in the BRI Incubator program by RKB BUMN in fostering MSMEs – MSMEs so that they can Go-Digital, Go-Modern and Go-Global. This research uses qualitative research methods with a phenomenological approach. The result of this study is that the public relations marketing strategy carried out by the BRI Incubator program consists of three types of strategies which consist of push strategy, pull strategy, and pass strategy. There is a strategy used to trigger MSMEs to grow into support until MSMEs get benefits that have been informed through BRI Incubator social media. However, the dissemination of information still focuses on Instagram social media followers only, so information related to the training held by the BRI Incubator has not been widely spread to the public with new types of MSMEs who want training to improve the quality of these MSMEs. so there is still a need for optimization so that there is an increase in the dissemination of information provided by the BRI Incubator program to other West Java MSMEs.